The small business survival guide - Reid, Jason (Boston, MA : Course Technoloy PTR, 2011)
Presents practical advice on getting a small business to grow, covering such topics as branding, marketing, sales, personnel management, customers, new technology, and business plans.
Includes bibliographical references and index.
Keywords: Small business -- Management